MicroRNAs identificados em parede ruminal de Bos indicus são modulados pela dieta e apresentam potenciais alvos em genes da microbiota ruminal - Porto, Thanny (Universidade Federal de São Carlos, 2023)
MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression both from the host and from its microbiota. miRNAs have the potential to influence the expression of phenotypes such as feed efficiency in beef cattle, as well as to modulate the composition and functionality of the microbiota in mammals. This project aims to identify the expression profile of miRNAs identified in rumen wall tissue in two groups of Nelore bulls (Bos indicus) submitted to different diets, i.e. conventional high-grain diet (n=26) and agricultural co-products diet (n=22). A total of 528 miRNAs were identified in the ruminal wall of the animals, nine of which were differentially expressed between the two treatment groups (FDR ≤ 0.1); seven miRNAs were up-regulated and two were down-regulated in the agricultural co-product fed group. Furthermore, our study also explores the potential regulation promoted by host miRNAs on ruminal microbiota genes. To investigate evidence of microbiota regulation by host miRNAs, we analyzed in silico the presence of bovine miRNA target sites in ribosome binding sites from Metagenome Assembled Genomes (MAGs) extracted from bovine ruminal contents. All nine differentially expressed miRNAs had predicted targets in MAGs’ genes. bta-miR-223 and bta-miR-874, potential regulators of feed efficiency and lipid metabolism, respectively, were more expressed in animals fed with co-products; and they target thirteen and 102 bacterial genes annotated in MAGs, respectively. The results presented here suggest that miRNAs identified in the ruminal wall of Bos indicus have their expression level modulated by the nutritional content of the animal’s diet. Furthermore, our findings support the hypothesis that ruminal microbiota genes have the potential to be regulated by Bos taurus miRNAs. Future work may indicate which phenotypes can be influenced through this regulation, as well as whether this regulation can be modulated in different nutritional interventions.
MicroRNAs identified in the ruminal wall of Bos indicus are modulated by diet and have potential targets in genes of the ruminal microbiota
Keywords: Bovinos; Ruminantes; Regulação genética; MicroRNAs; Microbiota; Cattle; Ruminants; Genetic regulation; MicroRNA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL